2015
DOI: 10.1016/j.jacc.2014.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Secretoneurin Is a Novel Prognostic Cardiovascular Biomarker Associated With Cardiomyocyte Calcium Handling

Abstract: SN provided incremental prognostic information to established risk indices in acute HF and ventricular arrhythmia-induced cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 26 publications
4
67
0
Order By: Relevance
“…1) (13). Four hundred seventy patients were included, and blood samples were available from 232 patients at ICU admission (median, 9 [Q1-Q3, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] hr from study inclusion to sampling) and from 201 patients after 72 hours.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1) (13). Four hundred seventy patients were included, and blood samples were available from 232 patients at ICU admission (median, 9 [Q1-Q3, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] hr from study inclusion to sampling) and from 201 patients after 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Other groups have also found secretoneurin to predict outcome after cardiac arrest (10). In contrast, admission secretoneurin levels were not associated with outcome in patients with acute exacerbations of chronic obstructive pulmonary disease (9), although these patients had comparable severity of dyspnea and mortality rates as the acute heart failure patients. Hence, secretoneurin seems to provide incremental prognostic information to established risk indices in patients with CVD, although not being an unspecific biomarker of disease severity per se.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, it is not established whether CgA fragments like CST may directly influence cardiomyocyte function. Although previous studies have reported that CST modulates cardiomyocyte Ca 2+ handling only via indirect mechanisms, 14 this finding is surprising given the direct effect of CST on Ca 2+ handling in noncardiac cells, 13 the influence by other chromogranin-secretogranin proteins on cardiomyocyte Ca 2+ handling, 15 and the ability of CST to directly interact with CaM. 13 CaM is an upstream activator of CaMKIIδ (Ca 2+ /CaM-dependent protein kinase IIδ), which is an established regulator of cardiomyocyte Ca 2+ handling.…”
Section: Ottesen Et Al Chromogranin a Processing And Calcium Regulationmentioning
confidence: 98%